Linoleate-pazopanib conjugation as active pharmacological ingredient to abolish hepatocellular carcinoma growth - Ke Wang; Ke Wang; Pei-Yin Liao; Wei-Chun Chang; Cian-Ru Yang; Yu-Ting Su; Ping-Ching Wu; Ping-Ching Wu; Ping-Ching Wu; Ping-Ching Wu; Yang-Chang Wu; Yao-Ching Hung; et al. (Frontiers in Pharmacology, 2024)
Small molecule compounds targeting multiple kinases involved in neoangiogenesis have shown survival benefits in patients with unresectable hepatocellular carcinoma (HCC). Nonetheless, despite the beneficial effects of multikinase inhibitors (MKIs), a lack of boosting adjuvant limits their objective response rate. Lipid conjugates have been used to improve delivery efficacy or pharmaceutical benefits for decades. However, the feasibility of utilizing lipid-drug conjugates (LDCs) in HCC regimens remains untested. In this study, oral feeding of linoleate-fluorescein isothiocyanate conjugates showed that the compound was well distributed in a spontaneous HCC mouse model. Therefore, a rationale design was developed for chemically synthesizing a linoleate-pazopanib conjugate (LAPC). The LAPC showed a significantly improved cytotoxicity compared to the parental drug pazopanib. Pazopanib’s angiogenic suppressing signals were not observed in LAPC-treated HCC cells, potentially suggesting an altered mechanism of action (MOA). In an efficacy trial comparing placebo, oral pazopanib, and LAPC treatments in the hepatitis B virus transgene-related spontaneous HCC mouse model (HBVtg-HCC), the LAPC treatment demonstrated superior tumor ablating capacity in comparison to both placebo and pazopanib treatments, without any discernible systemic toxicity. The LAPC exposure is associated with an apoptosis marker (Terminal deoxynucleotidyl transferase dUTP nick end labeling [TUNEL]) and an enhanced ferroptosis (glutathione peroxidase 4 [GPX4]) potential in HBVtg-HCC tumors. Therefore, the LAPC showed excellent HCC ablative efficacy with altered MOA. The molecular mechanisms of the LAPC and LDCs for HCC therapeutics are of great academic interest. Further comprehensive preclinical trials (e.g., chemical-manufacture-control, toxicity, distribution, and pharmacokinetics/pharmacodynamics) are expected.